Optimum Design of Load Capacity of Cycloidal Pin Wheel - Leilei Xu; Jianxin Su (Jixie chuandong)
Cycloidal pin wheel is the main component of RV reducer. In order to further improve the load capacity of RV reducer， a multi-objective optimization design method based on cycloid pinwheel contact stress and meshing stiffness is proposed. In order to optimize its load capacity， an optimization mathematical model with the minimum contact stress and the maximum meshing stiffness is constructed by taking the pin tooth distribution circle radius， short amplitude coefficient， pin diameter coefficient and cycloidal wheel width as design variables. Matlab is used to call the genetic algorithm in its optimization toolbox for solution. Compared with the original structure， the optimized structure reduces the contact stress， increases the meshing stiffness and improves the bearing performance， which provides a new method for the design of RV reducer.